Implementasi Pendidikan Karakter Peduli Lingkungan pada Siswa di SD Negeri 1 Suranenggala - Nisa, Nurul; Dewi, Dinie Anggraeni; Furnamasari, Yayang Furi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Pollution of the environment is a sign that people still care little about the environment. Schools and other educational institutions play a critical role in raising environmental consciousness among all age groups. The aim of this research is to ascertain the degree to which environmental awareness character education is being implemented at SD Negeri 1 Suranenggala, as well as the factors that facilitate and hinder this implementation. This study combines descriptive qualitative research with a qualitative methodology. Teachers, students, and principals were the subjects of the study. methods for gathering data include documentation, interviews, and observation. gathering, condensing, presenting, and making conclusions from data is data analysis. The implementation of environmental care character education at SDN 1 Suranenggala was demonstrated by the results. These included class pickets, clean Saturday events, classroom learning, the use of plastic bottle processing programs as planting media, the creation of ecobricks from plastic waste, and the development of the habit of disposing of trash in its proper place. Clear regulations, sufficient infrastructure, and helpful human resources (HR) are the supporting aspects. On the other hand, the things that are impeding are individual variances in character and the ignorance of teachers, parents, and students